Chemical optimization of benzo-dithiophene and benzo-[2, 1, 3]thiadiazole copolymers for the high performance, green-solvent-processed polymer solar cells. (October 2018) - Chen, YunXiang; You, Guofeng; Lin, Xinyu; Yuan, Xiyue; Zou, Ding; Wang, Wen; Yang, Renqing; Zhen, Hongyu; Ling, Qidan
Graphical abstract: With an alky thiophene and a bare thiophene as spacer, PBTTF-H exhibits high photovoltaic properties in the non-halogenated processed devices. Highlights: Three new BDF-FBT based polymers with different spacer were investigated. With an alky thiophone and a bare thiophone as the spacer, PBTTF-H performs best. A hexyl side chain leads a PCE gap of 5% between PBTTF-C6 and PBTTF-H based cells. Abstract: In this work, we demonstrate the chemical optimization of benzo[1, 2-b:4, 5-b′]dithiophene (BDT)-5, 6-difluorobenzo-[2, 1, 3]thiadiazole (FBT) D-A alternating copolymer for obtaining the efficient polymeric donors for the environment-friendly solution processed polymer solar cells (PSCs). Three polymers PBTF, PBTTF-C6 and PBTTF-H, in which one or two alky thiophene units are inserted into the backbone of BDT-FBT alternating copolymer, present much different performances either in the PSCs processed from halogenated solvent and additive or in the PSCs processed from non-halogenated solvent and additive. With an alky thiophene and a bare thiophene as the spacer, PBTTF-H performs best among the three. Especially when the devices processed from 1, 2, 4-trimethylbenzene and diphenyl ether, in which the highest PCE of 6.80% is achieved with a VOC of 0.77 V, a JSC of 13.67 mA cm −2 and a FF of 64.2%. We think these results will cast light on developing new polymeric donors of the green-solvent-processed PSCs.